Aerial work robot for a nuclear power plant with a pressurized heavy water reactor. (June 2016) - Shin, Hocheol; Kim, Changhoi; Seo, Yongchil; Jeong, Kyungmin; Choi, Youngsoo; Choi, Byungseon; Moon, Jeikwon
Highlights: The robot teleoperates a fuel handling machine of a nuclear power plant at high place. The robot can detect a leak from pipes placed at high spot. Radiation-hardened controllers and a camera are developed for the aerial work robot. Abstract: This paper presents an aerial work robot for a nuclear power plant (NPP) with a pressurized heavy water reactor (PHWR). The aerial work robot provides measurements by teleoperating a fuel handling machine placed at a high location in front of the PHWR. The robot can detect a leak from pipes such as delayed neutron (DN) monitoring tubes, which are also placed at a high place. The robot is equipped with radiation-hardened controllers, radiation-hardened cameras, and a noise robust communication system.